Kinetic role of a histidine residue in the T1 copper site of the laccase from Rigidoporus lignosus - Vianello, Fabio; Miotto, Giovanni; Cambria, Maria Teresa; Lima, Giuseppina P. P. [UNESP]; Vanzani, Paola; Di Paolo, Maria Luisa (Elsevier B.V., 2014)
Laccases (benzendiol:oxygen oxidoreductases; EC 1.10.3.2) catalyze the oxidation of a broad range of substrates, such as polyphenols, dyes and pollutants, and thus these enzymes are widely applied in industrial, biotechnological and environmental fields. In order to improve their biotechnological applications, a deep knowledge of structural factors involved in controlling their activity, in various experimental conditions and on different substrates, is required. In the present study, a laccase from the mushroom Rigidoporus lignosus was kinetically characterized. In particular, the stability, the effects of pH, ionic strength and fluoride ion concentration on the kinetic parameters were investigated, using three di-hydroxy-benzene isomers (1,2-dihydroxy-benzene, 1,3-dihydroxy-benzene and 1,4-dihydroxy-benzene) as substrates. The catalytic constant values of the laccase showed a bell-shaped pH profile, with the same optimum pH and pK(a) values for all tested substrates. This behavior appears to be due to the presence of an ionizable residue in the enzyme active site. To identify this residue, the enzyme was derivatized with diethylpyrocarbonate to modify accessible histidine residues, which, according to structural data, are present in the active site of this enzyme. The kinetic behavior of the derivatized laccase was compared with that of the native enzyme and the derivatized residues were identified by mass spectrometry. Mass spectrometry and kinetic results suggest the main role of His-457 in the control of the catalytic activity of laccase from R. lignosus. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Blu-copper laccase; Rigidoporus lignosus; pH profile; Ionic strength effects; Histidine modification; T1 copper site